Effect of maternal periconceptional undernutrition in sheep on cortisol regulation in offspring from mid-late gestation, through to adulthood - Oliver, Mark H.; Jaquiery, Anne L.; Connor, Kristin L.; Phua, Hui Hui; Harding, Jane E.; Thorstensen, Eric B.; Bloomfield, Frank H. (Frontiers in Endocrinology, 2023)
Maternal periconceptional undernutrition (PCUN) alters fetal hypothalamic-pituitary-adrenal function and placental glucocorticoid metabolism in sheep. The effects of PCUN on HPAA function in adult life are not known. We investigated the effects of PCUN on fetal adrenal development across gestation and on cortisol regulation in adult offspring. Ewes were undernourished from 61 days before to 30 days after conception (‘PCUN’) or fed ad libitum (‘N’). mRNA expression in the fetal adrenal gland of ACTH receptor (ACTHR), steroidogenic acute regulatory protein (STAR), cytochrome P450 17A1 (CYP17A1), 11beta-hydroxysteroid-dehydrogenase type 2 (11βHSD2), insulin-like growth factor-2 (IGF2), and in the fetal hippocampus of 11βHSD1, 11βHSD2, mineralocorticoid receptor (MR) and glucocorticoid receptor (GR) was determined at 50 (adrenal only), 85, 120 and 131 days of gestation (term=148 days). In adult offspring (≥ 3 years, N; 10 female, 5 male, PCUN; 10 female, 10 male) a combined arginine vasopressin (AVP, 0.1 μg/kg) and corticotropin-releasing hormone (CRH, 0.5 μg/kg) challenge and a metyrapone (40 mg/kg) challenge were undertaken. mRNA expression of ACTHR, STAR and CYP17A1 were determined in adult adrenals. Fetal adrenal STAR, CYP17A1 and IGF2 mRNA expression were not different between groups in early gestation but were higher in PCUN than N at 131 days’ gestation (all p<0.01). PCUN reduced fetal hippocampal MR and GR mRNA expression by 50% at 85 day, but not in later gestation. Adult offspring plasma cortisol responses to AVP+CRH or metyrapone were not different between groups. Plasma ACTH response to AVP+CRH was lower in PCUN males but ACTH response to metyrapone was not different between groups. Adult adrenal ACTHR, STAR, and CYP17A1 mRNA expression were not affected by PCUN. We conclude that the effects of PCUN on fetal HPAA function do are not reflected in adrenal cortisol secretion in mid-adulthood.